module Cat.Functor.Adjoint.Hom where

module _ {o ℓ o' ℓ'} {C : Precategory o ℓ} {D : Precategory o' ℓ'}
         {L : Functor D C} {R : Functor C D}
         where

Adjoints as hom-isomorphisms🔗

Recall from the page on adjoint functors that an adjoint pair LRL \dashv R induces an isomorphism

HomC(L(x),y)HomD(x,R(y)) \mathbf{Hom}_\mathcal{C}(L(x), y) \cong \mathbf{Hom}_\mathcal{D}(x, R(y))

of Hom\mathbf{Hom}-sets, sending each morphism to its left and right adjuncts, respectively. What that page does not mention is that any functors L,RL, R with such a correspondence — as long as the isomorphism is natural — actually generates an adjunction LRL \dashv R, with the unit and counit given by the adjuncts of each identity morphism.

More precisely, the data we require is an equivalence (of sets) f:HomC(Lx,y)HomD(x,Ry)f : \mathbf{Hom}_\mathcal{C}(Lx,y) \to \mathbf{Hom}_\mathcal{D}(x,Ry) such that the equation

f(gxLh)=Rgfxh f(g \circ x \circ Lh) = Rg \circ fx \circ h

holds. While this may seem un-motivated, it’s really a naturality square for a transformation between the bifunctors HomC(L,)\mathbf{Hom}_\mathcal{C}(L-,-) and HomD(,R)\mathbf{Hom}_\mathcal{D}(-,R-) whose data has been “unfolded” into elementary terms.

  hom-iso-natural
    : (∀ {x y}  C.Hom (L.₀ x) y  D.Hom x (R.₀ y))
     Type _
  hom-iso-natural f =
     {a b c d} (g : C.Hom a b) (h : D.Hom c d) x
     f (g C.∘ x C.∘ L.₁ h) ≡ R.₁ g D.∘ f x D.∘ h

  hom-iso→adjoints
    : (f :  {x y}  C.Hom (L.₀ x) y  D.Hom x (R.₀ y))
     (eqv :  {x y}  is-equiv (f {x} {y}))
     hom-iso-natural f
     L ⊣ R
  hom-iso→adjoints f f-equiv natural = adj' where
    f⁻¹ :  {x y}  D.Hom x (R.₀ y)  C.Hom (L.₀ x) y
    f⁻¹ = equiv→inverse f-equiv

    inv-natural :  {a b c d} (g : C.Hom a b) (h : D.Hom c d) x
                 f⁻¹ (R.₁ g D.∘ x D.∘ h) ≡ g C.∘ f⁻¹ x C.∘ L.₁ h
    inv-natural g h x = ap fst $ is-contr→is-prop (f-equiv .is-eqv _)
      (f⁻¹ (R.₁ g D.∘ x D.∘ h) , refl)
      ( g C.∘ f⁻¹ x C.∘ L.₁ h
      , natural _ _ _
      ∙ sym (equiv→counit f-equiv _)
      ∙ ap (f ⊙ f⁻¹)
           (D.extendl (ap (R.₁ g D._) (equiv→counit f-equiv _))))

We do not require an explicit naturality witness for the inverse of ff, since if a natural transformation is componentwise invertible, then its inverse is natural as well. It remains to use our “binaturality” to compute that f(id)f(\operatorname{id}_{}) and f1(id)f^{-1}(\operatorname{id}_{}) do indeed give a system of adjunction units and co-units.

    adj' : L ⊣ R
    adj' .unit .η x = f C.id
    adj' .unit .is-natural x y h =
      f C.id D.∘ h                    ≡⟨ D.introl R.F-id ⟩
      R.₁ C.id D.∘ f C.id D.∘ h       ≡˘⟨ natural _ _ _
      f (C.id C.∘ C.id C.∘ L.₁ h)     ≡⟨ ap f (C.cancell (C.idl _) ∙ C.intror (C.idl _ ∙ L.F-id))
      f (L.₁ h C.∘ C.id C.∘ L.₁ D.id) ≡⟨ natural _ _ C.id ⟩
      R.(L.₁ h) D.∘ f C.id D.∘ D.id ≡⟨ D.refl⟩∘⟨ D.idr _
      R.(L.₁ h) D.∘ f C.id          ∎
    adj' .counit .η x = f⁻¹ D.id
    adj' .counit .is-natural x y f =
      f⁻¹ D.id C.∘ L.(R.₁ f) ≡⟨ C.introl refl ⟩
      C.id C.∘ f⁻¹ D.id C.∘ L.(R.₁ f) ≡˘⟨ inv-natural _ _ _
      f⁻¹ (R.₁ C.id D.∘ D.id D.∘ R.₁ f) ≡⟨ ap f⁻¹ (D.cancell (D.idr _ ∙ R.F-id) ∙ D.intror (D.idl _))
      f⁻¹ (R.₁ f D.∘ D.id D.∘ D.id)     ≡⟨ inv-natural _ _ _
      f C.∘ f⁻¹ D.id C.∘ L.₁ D.id       ≡⟨ C.refl⟩∘⟨ C.elimr L.F-id ⟩
      f C.∘ f⁻¹ D.id                    ∎
    adj' .zig =
      f⁻¹ D.id C.∘ L.(f C.id)          ≡⟨ C.introl refl ⟩
      C.id C.∘ f⁻¹ D.id C.∘ L.(f C.id) ≡˘⟨ inv-natural _ _ _
      f⁻¹ (R.₁ C.id D.∘ D.id D.∘ f C.id) ≡⟨ ap f⁻¹ (D.cancell (D.idr _ ∙ R.F-id))
      f⁻¹ (f C.id)                       ≡⟨ equiv→unit f-equiv _
      C.id                               ∎
    adj' .zag =
      R.(f⁻¹ D.id) D.∘ f C.id          ≡⟨ D.refl⟩∘⟨ D.intror refl ⟩
      R.(f⁻¹ D.id) D.∘ f C.id D.∘ D.id ≡˘⟨ natural _ _ _
      f (f⁻¹ D.id C.∘ C.id C.∘ L.₁ D.id) ≡⟨ ap f (C.elimr (C.idl _ ∙ L.F-id))
      f (f⁻¹ D.id)                       ≡⟨ equiv→counit f-equiv _
      D.id                               ∎